2016
DOI: 10.1038/srep31045
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Biological Evaluation and Molecular Modeling Studies of New Oxadiazole-Stilbene Hybrids against Phytopathogenic Fungi

Abstract: Natural stilbenes (especially resveratrol) play important roles in plant protection by acting as both constitutive and inducible defenses. However, their exogenous applications on crops as fungicidal agents are challenged by their oxidative degradation and limited availability. In this study, a new class of resveratrol-inspired oxadiazole-stilbene hybrids was synthesized via Wittig-Horner reaction. Bioassay results indicated that some of the compounds exhibited potent fungicidal activity against Botrytis ciner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 48 publications
(59 reference statements)
2
10
0
Order By: Relevance
“…Inner vacuoles were found in 5j ‐treated hyphae, whereas this was rarely seen in the control mycelium. Similar results were observed in our previous study in which the mycelial cell membrane system was significantly damaged by the membrane permeability assay …”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Inner vacuoles were found in 5j ‐treated hyphae, whereas this was rarely seen in the control mycelium. Similar results were observed in our previous study in which the mycelial cell membrane system was significantly damaged by the membrane permeability assay …”
Section: Resultssupporting
confidence: 92%
“…In particular, the inhibition rates of compounds 5h and 5j at 200 µ g mL −1 were 47.5% and 48.4%, respectively, similar to that of fluopyram (47.1%). Interestingly, all the target compounds in this study containing a thiophene moiety had EC 50 values < 200 µ g mL −1 against B. cinerea , whereas only one fluorine‐containing compound displayed relative antifungal activity with an EC 50 value < 200 µ g mL −1 in our previously report . The results indicated that introduction of a thiophene moiety was favorable for antifungal activities.…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…Thus, new antiviral agents are required to efficiently inhibit influenza viruses. Stilbenes and chalcones are natural compounds characterized by several biological activities, including defense mechanisms in plants [7], fungicidal activity [8], antioxidant [9], chemopreventive [10] and cardioprotective effects [11], atherosclerosis [12], neurodegeneration [13], obesity [14] and diabetes control [15], and antimicrobial [16] and anticancer activities [17]. Analysis and reviews of the role of stilbenes in viral therapy [18], such as the inhibition of herpes simplex-1 (HSV-1), herpes simplex-2 (HSV-2) [19], respiratory syncytial (RSV) [20], human immunodeficiency (HIV) [21], varicella-zoster [22], and hepatitis C viruses [23], have been reported, including the activity against Influenza viruses [24].…”
Section: Introductionmentioning
confidence: 99%